2005
DOI: 10.1016/j.cognition.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Can infants attribute to an agent a disposition to perform a particular action?

Abstract: The present research investigated whether 13.5-month-old infants would attribute to an actor a disposition to perform a recurring action, and would then use this information to predict which of two new objects-one that could be used to perform the action and one that could not-the actor would grasp next. During familiarization, the infants watched an actor slide various objects forward and backward on an apparatus floor. During test, the infants saw two new identical objects placed side by side: one stood insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…In contrast to the 13.5-month-old infants in Song et al (2005), the 9.5-month-old infants in Experiment 1 who saw the short-and long-frame events tended to look equally. As we alluded to earlier, there were several possible interpretations for this negative result.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In contrast to the 13.5-month-old infants in Song et al (2005), the 9.5-month-old infants in Experiment 1 who saw the short-and long-frame events tended to look equally. As we alluded to earlier, there were several possible interpretations for this negative result.…”
Section: Discussionmentioning
confidence: 53%
“…The research summarized in the previous sections suggests that infants aged 5 months and older can attribute to an agent a predilection for a particular object (e.g., Luo & Baillargeon, 2005a, in review;Luo & Johnson, 2006;Repacholi & Gopnik, 1997;Song et al, in review); that infants aged 9 months and older can attribute to an agent a predilection for a particular agent (Kuhlmeier et al, 2003, in review); and that infants aged 13.5 months and older can attribute to an agent a predilection for a particular action (Song et al, 2005). The present research which built on these findings and asked whether 9.5-month-old infants might succeed in attributing to an agent a disposition involving a particular action.…”
Section: The Present Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more impressive, 6-and 10-month-old infants have been shown to prefer individuals who have demonstrated helping behavior over an individual who has shown hindering behavior, as demonstrated by their reaching and looking behavior (Hamlin et al, 2007). In another study that examined the ability to recognize the dispositions of others, Song, Baillargeon, and Fisher (2005) found that 13-month-old infants expected that an actor whom they had observed sliding various toys back and forth would select a new toy that afforded the same sliding motion. These findings suggest that infants can attribute a disposition to another on the basis of their behavior in one situation and expect their new behaviors to reflect that disposition.…”
mentioning
confidence: 99%